Examining Marital Infidelity via Game Theory - Limor Dina Gonen; Tchai Tavor; Uriel Spiegel (Mathematics, 2025)
Objective: Marital infidelity significantly impacts both the community and the institution of marriage. This study aims to develop a theoretical framework for analyzing marital infidelity through a game-theoretic lens. Methodology/Design/Approach: This research employs a game-theoretic model to predict the decision-making processes of unfaithful partners. Static game models are utilized to explore the interactions between spouses, focusing on identifying Nash equilibria that encapsulate the complexities and uncertainties inherent in infidelity-related decisions, whether through pure or mixed strategies. Results: The analysis reveals strategic dynamics in marital infidelity, where Nash equilibria indicate scenarios where one or both partners may engage in extramarital affairs. A Nash equilibrium is established when both partners perceive the benefits of infidelity as outweighing the costs, leading to diminished trust and communication. The Mixed-Strategy Nash Equilibrium (MSNE) hypothesis suggests that spouses may oscillate between fidelity and infidelity based on probabilistic strategies. Research Implications: This study provides a game-theoretic perspective on marital infidelity, whose findings may be used to inform legal frameworks and social policies addressing the consequences of infidelity, potentially impacting family counseling and legal services. Value/Originality: This research introduces a game-theoretic approach to understanding trust and transgression in marriages, identifying two primary categories of Nash equilibria. It fills a theoretical gap while providing practical insights into marital behavior.